STRUKTUR MIKRO DAN SIFAT MEKANIS ALUMINIUM (Al-Si) PADA PROSES PENGECORAN MENGGUNAKAN CETAKAN LOGAM, CETAKAN PASIR DAN CETAKAN CASTABLE - Martinus Mandala; Eddy Siradj; Sofyan Djamil (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Aluminum foundry is one of the business sectors that to much in demand by the public, ranging from small scale to large scale . Through remelting process, some small-scale aluminum casting industry, using raw materials of used aluminum as the main raw material. Some of the cast products are required to have good quality to comply with quality standards on its use. This study aims to look at the difference in quality of cast aluminum (Al-Si) using three types of mold, the metal mold, sand mold, and the mold castable by testing the mechanical properties of materials that impact and Brinell hardness testing. The method used was experimental or trial. The results obtained are the result cast using a metal mold has a hardness value of the highest of 63 HBN, with a value of impact 37